Critica del capitalismo e teoria dell’azione. Alasdair MacIntyre lettore di Karl Polanyi - Maletta, Santino Raffaele (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
This paper focuses on the relation between Alasdair MacIntyre and Karl Polanyi in the perspective of social philosophy. MacIntyre’s interpretation of the history of ethics in After Virtue explicitly requires the holistic and non-de-terministic narrative of modern history which is presented in Polanyi’s The Great Transformation. Moreover, the latter offers a comprehension of pre-modern times (i.e., previous to the industrial revolution) which is not affected by modern cultural and economic categories and by the “economic fallacy”. Both Polanyi and Mac-Intyre find in Aristotle the resources to overcome the crisis of modern ethics and economic theories. Lastly, going beyond Polanyi, MacIntyre founds on the category of “practice” an original critical social theory